2018
DOI: 10.4236/oju.2018.83009
|View full text |Cite
|
Sign up to set email alerts
|

Elastosonographic Changes in Patients with Peyronie's Disease, before and after Treatment with a Compound Based on <i>Ecklonia bicyclis</i>, <i>Tribulus terrestris</i>, and Water-Soluble Chitosan

Abstract: Several diagnostic techniques have been proposed during the time for the diagnostic evaluation of Induratio Penis Plastica (IPP), due to poor sensitivity and specificity of standard B-Mode Ultrasonography. Shear-Wave elastosonography (SWE) is a relative new ultrasound technique, already used for several organs, which allows evaluating the rigidity of the tissues. Furthermore, we used a compound consisting of Ecklonia bicyclis, Tribulus terrestris, and Biovis (water-soluble Chitosan) with antifibrotic and antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Regarding the clinical use of shear-wave elastography (SWE) in patients with PD, we found five articles in the literature where this method was used. The authors of these articles have indicated that this technique is very useful for identifying non-palpable or nondetectable plaques with simple ultrasound equipment, as well as for monitoring changes in plaque rigidity during and after conservative treatments [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the clinical use of shear-wave elastography (SWE) in patients with PD, we found five articles in the literature where this method was used. The authors of these articles have indicated that this technique is very useful for identifying non-palpable or nondetectable plaques with simple ultrasound equipment, as well as for monitoring changes in plaque rigidity during and after conservative treatments [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors carried out a study on 40 patients with Peyronie’s disease using elastosonographic imaging and employing the shear-wave elastography (SWE) technique to assess the tissue stiffness of the cavernous bodies [ 42 ]. The measurements were conducted using the GE Logic S8 ultrasound machine (GE/General Electric, Chicago, IL, USA) equipped with a linear probe and using a 10 MHz frequency.…”
Section: Relevant Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we propose that these data were very different because they were collected in the year 1976 and solely through palpation, without the use of penile ultrasound. Today, thanks to the technical evolution of ultrasound machines and with the help of elastography, it is possible to identify non-palpable penile plaque [ 91 , 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%